Context-dependent agricultural intensification pathways to increase rice production in India - Hari S. Nayak; McDonald, Andrew J.; Kumar, Virender; Craufurd, Peter Q.; Dubey, Shantanu Kumar; Nayak, Amaresh Kumar; Parihar, Chiter Mal; Panneerselvam, Peramaiyan; Poonia, Shishpal; Fantaye, Kindie Tesfaye; Malik, Ram K.; Urfels, Anton; et al. (Nature Publishing Group, 2024)
Yield gap analysis is used to characterize the untapped production potential of cropping systems. With emerging large-n agronomic datasets and data science methods, pathways for narrowing yield gaps can be identified that provide actionable insights into where and how cropping systems can be sustainably intensified. Here we characterize the contributing factors to rice yield gaps across seven Indian states, with a case study region used to assess the power of intervention targeting. Primary yield constraints in the case study region were nitrogen and irrigation, but scenario analysis suggests modest average yield gains with universal adoption of higher nitrogen rates. When nitrogen limited fields are targeted for practice change (47% of the sample), yield gains are predicted to double. When nitrogen and irrigation co-limitations are targeted (20% of the sample), yield gains more than tripled. Results suggest that analytics-led strategies for crop intensification can generate transformative advances in productivity, profitability, and environmental outcomes.